Disclosing the Potential of Fluorinated Ionic Liquids as Interferon-Alpha 2b Delivery Systems - Ferreira, Margarida L. (2022)
Funding: This research was funded by FCT/MCTES (Portugal) through grants SFRH/BD/130965/2017 and COVID/BD/151919/2021 (M.L.F.), the contracts of Individual Call to Scientific Employment Stimulus 2020.00835.CEECIND (J.M.M.A.)/2021.01432.CEECIND (A.B.P.) and project PTDC/EQU-EQU/2223/2021. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.